Karrikin and cyanohydrin smoke signals provide clues to new endogenous plant signaling compounds - Flematti, G.; Waters, M.; Scaffidi, A.; Merritt, D.; Ghisalberti, E.; Dixon, Kingsley; Smith, S. (2013)
Two new types of signaling compounds have been discovered in wildfire smoke due to their ability to stimulate seed germination. The first discovered were karrikins, which share some structural similarity with the strigolactone class of plant hormones, and both signal through a common F-box protein. However, karrikins and strigolactones operate through otherwise distinct signaling pathways, each distinguished by a specific α/β hydrolase protein. Genetic analysis suggests that plants contain endogenous compounds that signal specifically through the karrikin pathway. The other active compounds discovered in smoke are cyanohydrins that release germination-stimulating cyanide upon hydrolysis. Cyanohydrins occur widely in plants and have a role in defense against other organisms, but an additional role in endogenous cyanide signaling should also now be considered.